The prisoner of Zenda. - Hope Anthony; Hackett, James Keteltas, 1869-1926.; Hope, Anthony, 1863-1933.; Famous Players Film Co.; Gaiety Theatre (Organization : New York, N.Y.); Theater Playbills and Programs Collection (Library of Congress) (New York : Kraus Mgf. Co., 1913)
Daniel Frohman presents James K. Hackett and his special company in the dramatic masterpiece of romance and adventure "The Prisoner of Zenda," in motion pictures produced by the Famous Players Film Company, Adolph Zukor, Pres.
Gaiety Theatre [Washington, D.C.], three days, June 5-6-7, matinee every day 2:30. [1913?]
Title devised by Library staff.
In: American theater programs of the late 19th and 20th centuries (Library of Congress).
Keywords: Advertising postcards